DAMPAK DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI GH UNIVERSAL HOTEL BANDUNG - Kurniasih, Imas Wiwin; Bastian, Zein; Parwitasari, Nur Aini; Ambiapuri, Ema (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
The performance index of active employees working at GH Universal Hotel Bandung from 2016 to 2019 showed a decline. One factor suspected to be the cause of this decline is Work Discipline, due to the lack of achievement of attendance targets, which was considered static for four years, from 2016 to 2019. This study aims to measure the assessment of Work Discipline on Employee Performance at GH Universal Hotel Bandung. The research subjects were permanent and contract employees working at GH Universal Hotel Bandung in 2020. From a population of 138 employees, a sample of 103 respondents was taken. Data collection was conducted through questionnaires. The method used in this study was quantitative and explanatory, utilizing simple linear regression analysis. The results showed a positive and significant impact between Work Discipline and employee performance at GH Universal Hotel Bandung.